Impact of Microfinance on Fertilizer Use in the Ayeyarwady Region, Myanmar - Yee, Hnin Wut; Ridwan, Endrizal; Muharja, Fajri; Kamarni, Neng (Jurnal Informatika Ekonomi Bisnis, 2023)
This research aims to analyze the impact of microfinance on fertilizer use and the amount of loan in the Ayeyarwady area, Myanmar. This study uses a quantitative technique as an analytical approach, utilizing data from a farmers' household survey conducted in 2015 as secondary data. Secondary data from a village tract in Myanmar's Ayeyarwady area. The overall frequency of gender of the household, education level of the household, age of the household, percentages of loan amount from each family, and average cost of usage per acre are all survey data used in this study. The outcome revealed the microfinance institution, as well as the overall proportion of demographic respondents from the Ayeyarwady area. An assessment into how the money was utilized in agricultural output, on the other hand, revealed that the respondents from credit beneficial used at all of the loan for agricultural purpose. The findings of this study must reveal the impact of microfinance on fertilizer use, as well as the strengths and shortcomings of microfinance. The results indicated the microfinance institution as well as the general proportion of demographic respondents from Ayeyarwady. An examination of how the money was used in agricultural production, on the other hand, found that credit advantageous respondents used at all of the loan for agricultural purposes. This study's findings must indicate the impact of microfinance on farmers.